2019
DOI: 10.1136/bmjopen-2019-030845
|View full text |Cite
|
Sign up to set email alerts
|

Public understanding and use of antibiotics in England: findings from a household survey in 2017

Abstract: ObjectivesTo describe public understanding and use of antibiotics.DesignIpsos MORI Capibus survey of randomly-selected households.SettingEngland, January–April 2017.Participants2283 adults (≥15 years) including 777 parents of children <5 years old.Data collection and analysisThe main survey was undertaken in January 2017 (n=1691); data from an additional sample of parents were collected in April 2017 (n=592). Analyses were weighted to obtain estimates representative of the population.Main outcome measuresRespo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 27 publications
3
31
0
1
Order By: Relevance
“…HCPs’ concerns around patients’ expectations for antibiotics align with previous research [ 37 ]; however, patients in our study had better knowledge of appropriate antibiotic use in comparison with the qualitative literature [ 23 , 24 , 25 , 26 , 27 , 38 , 39 , 40 ], which was conducted mainly before 2012. Since 2012, there has been greater emphasis on public education via national AMR campaigns, support for GPs with AMS tools [ 18 ], and incentives for Clinical Commissioning Groups around improvements in antibiotic prescribing (Quality Premiums) [ 41 ], which may have caused this attitude shift.…”
Section: Discussionsupporting
confidence: 64%
“…HCPs’ concerns around patients’ expectations for antibiotics align with previous research [ 37 ]; however, patients in our study had better knowledge of appropriate antibiotic use in comparison with the qualitative literature [ 23 , 24 , 25 , 26 , 27 , 38 , 39 , 40 ], which was conducted mainly before 2012. Since 2012, there has been greater emphasis on public education via national AMR campaigns, support for GPs with AMS tools [ 18 ], and incentives for Clinical Commissioning Groups around improvements in antibiotic prescribing (Quality Premiums) [ 41 ], which may have caused this attitude shift.…”
Section: Discussionsupporting
confidence: 64%
“…The questionnaire was based on the previously published PHE public survey questionnaires around antibiotics ( online supplemental appendix 1 ). 12 Questions were developed in collaboration with general practitioners (GPs), non-healthcare advisors, PHE’s marketing team and Ipsos Market and Opinion Research International (MORI) health questionnaire team, and formed part of a larger survey asking about hygiene and health-seeking behaviour for infections. To allow consistency and to facilitate comparison with previous surveys, many of the questions were asked in an identical manner to the surveys in 2014 and 2017, with the new questions in 2020 covering understanding about antibiotic resistance and the usefulness of antibiotics for different conditions added at the end so that inclusion of new questions did not disrupt the compatibility of subsequent questions with previous years’ results.…”
Section: Methodsmentioning
confidence: 99%
“… 5 10–12 The 2017, public survey highlighted some misunderstanding about the activity of antibiotics and found that black, Asian and minority ethnic (BAME) and younger groups reported less knowledge and greater antibiotic use. 12 Since 2017 the Keep Antibiotics Working campaign 10 and development of patient facing resources for use by community pharmacists and primary healthcare professionals have continued, 13 but we do not know if these have influenced the publics’ attitudes to antibiotics. This report presents the findings of the January/February 2020 household survey undertaken before the first UK COVID-19 pandemic lockdown and has an additional focus on BAME, to explore the differences highlighted in the 2017 survey.…”
Section: Introductionmentioning
confidence: 99%
“…Limited public awareness about the differences between a viral and bacterial infection alongside beliefs that antibiotics are low risk medications are drivers of unnecessary prescriptions in the outpatient setting. 18 Patients and the general public are more receptive to communication that stresses the effect of antibiotic overuse on the individual, rather than harms to society.…”
mentioning
confidence: 99%